Studies on repeat breeding in relation to some biochemical alterations during oestrus cycle of crossbred cows - SHUKLA, S P; SHARMA, R D; SRIVASTAVA, A K (The Indian Journal of Animal Reproduction, 2023)
Biochemical changes during different stages of oestrus cycle in 10 normal and 45 repeat breeding cows were determined. In normal animals increase in serum concentrations of aspartate amino transferase, alanine amino transferase, acid phosphatase, lactate dehydrogenase and adenosinetriphosphatase enzymes were observed from O to 16th day of oestrous cycle (P=0.5). The pattern ofchanges in serum enzymes was similar in repeat breeders but the extent of elevation of the enzymes except for ATPase was 2-4 folds higher than that of normal animals. In repeat breeders, the rise in serum levels of ATPase (21-36%) was 2-3 fold less than that of normal animals ( 46%). There was no significant alteration in the serum concentrations ofalkaline phosphatase, total protein and creatinine during oestrus cycle between normal and repeat breeder animals.
Keywords: Repeat Breeding; Biochemical alterations; Cows; Enzymes; Proteins; Oestrous cycle